Propuesta metodológica para la medición de la satisfacción de usuarios de internet móvil en Colombia (2019)
In the most recent update to the Regime for the Protection of Users’ Rights of Communications Services, the requirement was included that operators should monitor user satisfaction with respect to each of the means of attention through the indicator called Net Promoter Score (NPS). The NPS, despite being a widely used indicator in various sectors, in this case it only inquires about user satisfaction against the attention received by a certain channel and it does not allow to have a general view of user satisfaction that covers all aspects and moments of service provision. In the investigation development, a model for measuring the satisfaction of mobile internet users is proposed, which in addition to containing the NPS, allows to measure the satisfaction users of the mobile internet service in a representative and comparable way in the main cities of Colombia, covering the user experience in all phases of the service provision cycle